Effects of ketamine use on psychotic disorders and symptoms in male, methamphetamine-dependent subjects - Dong, Huixi; Yang, Cheng; Shen, Yidong; Liu, Liang; Liu, Mengqi; Hao, Wei (The American journal of drug and alcohol abuse, 2019)
Background: Repeated and extensive methamphetamine or ketamine use may cause psychotic symptoms. Whether the chronic and combined use of these substances has a greater psychotic effect is still unknown. Objectives: To examine the effect of different levels of ketamine use on psychotic disorders and symptoms in male methamphetamine-dependent subjects. Methods: A cross-sectional, structured, and clinical interview method was used to examine the differences in DSM-IV-TR Axis I psychotic disorders and symptoms among methamphetamine-dependent subjects in three categories: 205 with no ketamine use, 38 with occasional ketamine use, and 72 with ketamine abuse or dependence from compulsory rehabilitation centers. Results: Both methamphetamine-dependent subjects with occasional ketamine use and those with ketamine abuse or dependence had a higher prevalence of psychotic disorders than those who had not used ketamine (p = 0.021; p < 0.001). Subjects who used ketamine occasionally had a higher prevalence of referential and persecutory delusions (p < 0.001; p = 0.013) and auditory hallucinations (p = 0.030), and those with ketamine abuse or dependence had a higher prevalence of referential and persecutory delusions (p = 0.005; p = 0.021), compared with those who had not used ketamine. There was no significant difference in any psychotic disorders or symptoms between subjects with occasional ketamine use and those with ketamine abuse or dependence. Conclusions: The combination of methamphetamine and ketamine was associated with greater psychotic effects than methamphetamine alone. Both occasional ketamine use and ketamine abuse or dependence were associated with increased psychotic symptoms and disorders in methamphetamine-dependent males.